Ostrich (Struthio camelus ) Egg Embryonic Death During Artificial Incubation - Faki, Aisha E.; Obeid, E.A.E.; Osman, Hagir I.M.; Amin, A.E (International Journal of Applied Sciences and Biotechnology, 2015)
Intensification of ostrich farming revealed that egg hatchability was remarkably lower than the wild. This review considers the factors leading to, as pertaining to the ostrich, egg and incubator. Ostrich genotype, age, season and congenital problems affect clutch and egg sizes and egg quality- fertility to lead a successful hatch. Egg treatment prior incubation can later reduce hatchability, affected by storage conditions and duration. Most detrimental factors lie in the incubator and hatcher management. Egg correct positioning and turning in the appropriate incubator humidity and temperature are likely to yield high hatch. Variability in egg size, shell quality, pore sizes and numbers govern the water loss and exchange of gases. The hatcher management is important when chicks need intervention. Dead-in-shell embryos, early or late were likely to be affected by all of the above factors plus egg microbial contamination or be merely nutritional. Int J Appl Sci Biotechnol, Vol 3(4): 566-578